2008
DOI: 10.1111/j.1467-9663.2008.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

How Different Are Activities While Commuting by Train? A Case in Tokyo

Abstract: Generally, travel is considered a demand derived from the desire to engage in activities at destinations and travel time is also considered a wasteful time. However, if people can engage in activities while travelling, travel time is not just a wasteful time but could be a productive time. In recent years, ICTs provide travellers with various activity opportunities while travelling. This paper examined what activities train commuters were engaging in while travelling and what factors of travel environment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 23 publications
1
75
0
1
Order By: Relevance
“…Hence, different results between Thomas's and the current study may arise from the different methods used. Ohmori and Harata (2008), Thomas (2009), and the current study. …”
Section: Observing Passengers Over Timementioning
confidence: 48%
See 2 more Smart Citations
“…Hence, different results between Thomas's and the current study may arise from the different methods used. Ohmori and Harata (2008), Thomas (2009), and the current study. …”
Section: Observing Passengers Over Timementioning
confidence: 48%
“…Ohmori and Harata's observer recorded six to eight passengers' activities every minute (Ohmori and Harata 2008). Our study showed a researcher can comfortably observe two people at a time.…”
Section: Observing Passengers Over Timementioning
confidence: 79%
See 1 more Smart Citation
“…For instance, abundant activities (e.g., online shopping, telecommuting, online entertainment, etc.) occur at home and the function of home has been redefined (Hjorthol & Gripsrud, 2009;Ohmori & Harata, 2008;Zhen & Wei, 2008). ICTs improve the tempo-spatial flexibility of residents' activities and lead to changes in the relationship between activities and places.…”
Section: Introductionmentioning
confidence: 99%
“…For example, car drivers have been observed to hoard curbside parking places (Shoup, 2005, p. 443); students have been reported to hoard university computers (Straathof, 2011); airlines have been observed to hoard landing 1 See Gilbert and Hudson (2000), Lyons and Urry (2005), Small and Verhoef (2007), Ohmori and Harata (2008) and Proost and Dender (2008). 2 See Currie and Yelowitz (2000), Doganis (2002), Shoup (2005), Arnott and Inci (2006); Givoni and Rietveld (2009) and Van Ommeren and Koopman (2011). slots at airports (Doganis, 2002).…”
mentioning
confidence: 99%